2018
DOI: 10.1101/303529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting glutamine metabolism and redox state for leukemia therapy

Abstract: Acute myeloid leukemia (AML) is a hematological malignancy characterized by the accumulation of immature myeloid precursor cells. AML is poorly responsive to conventional genotoxic chemotherapy and a diagnosis of AML is usually fatal.More effective and less toxic forms of therapy are desperately needed. AML cells are known to be highly dependent on the amino acid glutamine for their survival. Here, we show that blocking glutamine metabolism through the use of a glutaminase inhibitor (CB-839) significantly impa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 40 publications
(53 reference statements)
3
31
0
Order By: Relevance
“…Our results are in agreement with numerous studies showing either distinct metabolic fuel choice and dependency based on distinct molecular signature [ 15 ] or glutamine uptake in GBM in vivo using PET imaging based on 18 F-Fluoroglutamine [ 16 ]. Furthermore, several reports have shown that many tumors rely on glutamine to fuel TCA cycle in vivo, in agreement with glutamine dependency observed in corresponding in vitro models [ 17 19 ]. Reliance of mesenchymal GBM on glutamine metabolism in vivo is reinforced by the inhibition of key nodes in glutamine metabolism which retards tumor growth in our preclinical models.…”
Section: Discussionsupporting
confidence: 81%
“…Our results are in agreement with numerous studies showing either distinct metabolic fuel choice and dependency based on distinct molecular signature [ 15 ] or glutamine uptake in GBM in vivo using PET imaging based on 18 F-Fluoroglutamine [ 16 ]. Furthermore, several reports have shown that many tumors rely on glutamine to fuel TCA cycle in vivo, in agreement with glutamine dependency observed in corresponding in vitro models [ 17 19 ]. Reliance of mesenchymal GBM on glutamine metabolism in vivo is reinforced by the inhibition of key nodes in glutamine metabolism which retards tumor growth in our preclinical models.…”
Section: Discussionsupporting
confidence: 81%
“…To sustain high proliferative advantage, LSCs may adapt a metabolic preference for glutamine to drive biomass. This so-called glutamine addiction has been demonstrated in multiple studies and represents a potential target for anti-leukemic therapy[ 20 - 23 ].…”
Section: Leukemic Stem Cell Metabolismmentioning
confidence: 99%
“…We focused on IRE1α and PERK, well-known participants in inducing apoptosis. Indeed, PERK has been shown to inhibit the translation initiation factor 2α (eukaryotic initiation factor 2 alpha (eIF2α) by phosphorylation, thereby, reducing protein synthesis and overload [ 23 , 24 , 25 ]. In accordance, our results revealed rapid phosphorylation of eIF2α in MV-4-11 cells within 15 min following VAS3947 exposure ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the authors showed that the survival of ROS low LSCs is dependent on the availability of cysteine. The combination of arsenic trioxide (ATO) and homoharringtonine (HHT), drugs that perturb the mitochondrial redox state, with CB-839, a drug that blocks glutamine metabolism and consequently GSH production, efficiently induced cell death of AML cell lines, primary AML patient-derived samples, and in vivo mice models of AML [ 25 ]. Additionally, other studies showed that glutathione peroxidases (GPX)-1 and GPX-3, two antioxidant enzymes requiring GSH to detoxify hydrogen peroxide, are highly involved in AML development [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%